Characterization on the cardiac function of hypothermic dogs from cold water immersion - Chengxiang Lei; Jiangzhou Ding; Gaochao Si; Hui Zhang; Wei Zhu; Zhiyong Peng; Wei Wang (Актуальні проблеми транспортної медицини, 2011)
OBJECT To clarify the effects of cold water immersion on the canine cardiac function and how to prevent the immersed hypothermic ventricular fibrillation. METHODS 7 normal male dogs, which were randomly divided into two groups, the experimental (3, each with 2.5mg/kg nimodipine) and the control (4), were immersed in cold water at 6 ± 1!. The polygraph system was used to record the cardiac function and the transmission electron microscope was involved to study the ultrastructure changes of myocardium. The activity levels of Na⁺:K⁺:ATPase and Ca²⁺:ATPase were measured by means of Elisa. RESULTS As the canine core temperature going down, it was noted that the left ventricular pressure peak value (LVSP), and the isovolumetric contraction phase maximal ascending/descending velocity ( ± dP/dtmax) decreased evidently, with a prolonged Q:T duration, and that hypothermic J waves were found subsequently. The activities of Na⁺:K⁺:ATPase and Ca²⁺ATPase were both inhibited. There came rapid ventricular arrhythmia with the control dogs, while not with the experimental. CONCLUSIONS The hypothermia would result in the weakening of canine cardiac function, moreover, the appearance of J wave might be followed by the occurrence of hypothermic ventricular fibrillation. The results also suggested that nimodipine might have a potential to prevent immersed hypothermic ventricular fibrillation. Для уточнення наслідків занурення в холодну воду на функції серця собак і запобігання викликаної гіпотермією фібриляції шлуночків 7 нормальних псів, які були випадковим чином розділені на дві групи (дослідну і контрольну), були занурені в холодну воду при 6 ± 1 ° С. Тварини експериментальної групи попередньо отримали 2,5 мг/кг німодипіну. Для запису функції серця використовували систему поліграф. Для дослідження ультраструктури змін міокарда використовували просвічуючу електронну мікроскопію. Рівні активності Na⁺/K⁺АТФази і Ca²⁺:АТФази були виміряні за допомогою ELISA.При падінні температури тіла собак було відзначено, що пікове значення тиску лівого шлуночка (LVSP) та ізоволюметрічна фаза скорочення максимального зростання/убування швидкості зменшилася. Активності Na⁺/K⁺:АТФази і Ca²⁺:АТФази знижувалися. При цьому у контрольних собак спостерігалася, а у досвідчених не спостерігалася швидка шлуночкова аритмія. Показано, що гіпотермія може призвести до ослаблення функції серця собак, крім того, за появою J хвилі може послідувати виникнення викликаної гіпотермією фібриляції шлуночків. Результати дозволяють припустити, що німодипін, можливо, здатний запобігти фібриляції шлуночків, яка викликана гіпотермією. Для уточнения последствий погружения в холодную воду на функции сердца собак и предотвращения вызванной гипотермией фибрилляции желудочков 7 нормальных кобелей, которые были случайным образом разделены на две группы (опытную и контрольную), были погружены в холодную воду при 6 ± 1 °С. Животные экспериментальной группы предварительно получили 2,5 мг/кг нимодипина. Для записи функции сердца использовали систему полиграф. Для исследование ультраструктуры изменений миокарда использовали просвечивающую электронную микроскопию. Уровни активности Na⁺/K⁺:АТФазы и Ca²⁺:АТФазы определяли с помощью ELISA. При падении температуры тела собак было отмечено, что пиковое значение давления левого желудочка (LVSP) и изоволюметрическая фаза сокращения максимального возрастания/убывания скорости уменьшилась. Активности Na⁺/K⁺:АТФазы и Ca²⁺:АТФазы снижались. При этом у контрольных собак наблюдалась, а у опытных не наблюдалась быстрая желудочковая аритмия. Показано, что гипотермия может привести к ослаблению функции сердца собак, кроме того, за появлением J волны может последовать возникновение вызванной гипотермией фибрилляции желудочков. Результаты позволяют предположить, что нимодипин, возможно, способен предотвратить фибрилляции желудочков, вызванные гипотермией.